Elastic field near the tip of an anticrack in a decagonal quasicrystalline material - Wang, Xu; Schiavone, P. (Applied mathematics and mechanics, 2020)
We investigate the elastic field near the tip of an anticrack in a homogeneous decagonal quasicrystalline material subject to plane strain deformations. The phonon and phason stresses exhibit a square root singularity at the anticrack tip. Two real-valued phonon stress intensity factors and two real-valued phason stress intensity factors are introduced to scale four separate modes of deformation. We obtain four analytic functions which completely characterize the induced phonon and phason stresses as well as the displacement field. In particular, we derive a concise yet elegant representation of the anticrack contraction force.